Zero energy building in Malaysia / Mohd Ridhwan Mohd Rodzi - Mohd Rodzi, Mohd Ridhwan (Faculty of Architecture, Planning and Surveying, 2010)
This thesis is study on office building according to local climate in Malaysia. It concerned mostly about energy efficiency level in office building. The main focus of this dissertation is how can we save the energy consumption in the building and be environmental friendly. The concept of the zero energy office building is a combination of two technique of construction technology which is intelligent building and the green building. Each of these leading edge case study building demonstrates the progress toward achieving zero energy use goal because it Is a building with a technology. A strategy for sustainable construction is a significant milestone on the road to a more socially and environmentally responsible. It creates a framework within which the industry can make a strong contribution to the better future. In this dissertation is to study the energy efficiency and how to reduce energy consumption in zero energy building. The building are Mesiniaga building, Malaysia Energy Center, Malaysia Securities Commission, Ministry of Energy, Water and Technology and GTower. From this dissertation, I hope can give some input for the better next construction to save our environment and nature.